UV and visible photodetection of Al-doped ZnO on p-Si prepared by pulsed laser deposition - Kek, Reeson; Nee, Chen Hon; Yap, Seong Ling; Tou, Teck Yong; Arof, Abdul Kariem; Koh, Song Foo; Yap, Seong Shan (IOP Publishing, 2018)
Al-doped ZnO (AZO) thin films were deposited on p-Si (100) by pulsed laser deposition at room temperature to form AZO/p-Si heterojunctions. Crystalline films with different properties were obtained. The heterojunctions exhibit diode behavior in dark and responded to illumination of broadband visible (400 nm ∼ 750 nm) and/or ultraviolet (368 nm) light in applied voltage range of only ±1 V. Visible photons are mostly absorbed in p-Si and UV photons were absorbed in AZO layer. However, the defects level within the bandgap of the AZO layer would also contribute to photocurrent under visible light illumination. The best photodetection was obtained for AZO with resistivity of 1 Ωcm and low defects density where the sample response to either UV or visible light by changing the biasing voltage from -1 V or +1 V.